2022
DOI: 10.3390/children9060893
|View full text |Cite
|
Sign up to set email alerts
|

Management of Harlequin Ichthyosis: A Brief Review of the Recent Literature

Abstract: Harlequin ichthyosis (HI) is a life-threatening genetic disorder that largely affects the skin of infants. HI is the most severe form of the autosomal recessive disorder known as ichthyosis. It is caused by mutations in the A12 cassette (lipid-transporter adenosine triphosphate-binding cassette A12). Neonates affected by this disease are born with specific morphological characteristics, the most prominent of which is the appearance of platelet keratotic scales separated by erythematous fissures. The facial fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 61 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…Hence, it should be a reminder for surgical intervention using autologous skin grafts with the utmost care, physiotherapy, analgesia for painful deep fissures, and proper infection control. 16 Eye care by artificial tears lubrication and frequent evaluation by ophthalmologists is recommended. Repeated blockage of the ear canal may occur, and debridement is often required.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it should be a reminder for surgical intervention using autologous skin grafts with the utmost care, physiotherapy, analgesia for painful deep fissures, and proper infection control. 16 Eye care by artificial tears lubrication and frequent evaluation by ophthalmologists is recommended. Repeated blockage of the ear canal may occur, and debridement is often required.…”
Section: Discussionmentioning
confidence: 99%
“…They also pointed out that Vitamin D intake should be considered to avoid the retinoids’ side effects. 9 …”
Section: Discussionmentioning
confidence: 99%
“…In their review, surgical interventions were reported to treat eyelids and the digits’ necrosis. 9 Previous research suggested early surgery has a beneficial therapeutic effect in HI cases. 44 , 45 No evidence was found that early surgery resulted in less ectropion at 6–12 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations